Impact of Psychological and Social Determinants on Health - Mehboob, Riffat (Pakistan Journal of Health Sciences, 2023)
The World Health Organization defines the Social Determinants of Health (SDH) as "the conditions under which people are born, grow, work, live, and age, as well as the broader set of forces and systems influencing the conditions of daily life". Psychosocial variables and social determinants both have an important role in determining a person's health and well-being. The psychological, social, and cultural dimensions of these issues can have an impact on a person's behavior and health. Stress, education, poverty, social exclusion, discrimination, and violence are a few examples of these psychosocial determinants. These elements can be protective or, on the other hand, raise the risk of physical and mental illness and lower people's quality of life. Social determinants of health are a combination of social, economic, and physical factors. They play a role in determining the patterns of illness, disease, and health that are observed in a population. They establish the circumstances in which people are conceived, develop, live, work, and age. Health and medical care, economic security, social and communal context, local geography and built environment, and education are all examples of social determinants of health. The connection between individuals and their social and physical environments frequently worsens poor health outcomes. Low socioeconomic position, unemployment, strained family ties, and hazardous neighborhoods have been shown in studies to have a significant negative impact on mental health. Additionally, those who suffer from severe psychological disorders are more probable to experience social segregation, poverty, food insecurity and housing uncertainty all of which can decrease quality of life and hamper rehabilitation. Pakistan experienced the largest gain among the SAARC nations between 2013 and 2018, increasing its happiness score by 26 points, and is expected to rank among the top 20 gainers globally in 2020 [2]. However, it lowers to 4.934from 2018-2020 and is ranked 105 out of 149 happiest countries. There could be a number of causes for this downward tendency. The need of the hour is to pinpoint the causes of Pakistan's declining happiness level. These findings would help policymakers get rid of or manage the factors contributing to people's lower levels of happiness. It is improbable to understate the importance of social and psychological factors in determining health. Healthcare systems and politicians may create initiatives that successfully promote well-being, lessen health inequities, and enhance overall health outcomes by understanding and addressing these variables. A healthier and more equal society must be built via comprehensive strategies that incorporate socioeconomic inequities and mental health care. In order to promote a more inclusive and sustainable society, the international community is making great progress towards reaching many Sustainable Development Goals (SDGs). We are covering several SDGs described by United Nations which include: SDG 1, “No Poverty”; SDG 2, "Zero Hunger"; SDG 3, "Good Health and Well-being"; SDG 4, "Quality Education"; SDG 5, "Gender Equality"; SDG 8, "Decent Work and Economic Growth" and SDG 10, "Reduced Inequalities". The elimination of poverty, hunger, and inequality, as well as the promotion of sustainable economic growth, are the top priorities behind these objectives. By achieving these objectives, we can collectively work towards a more sustainable and equitable future in which no one is left behind.